2002
DOI: 10.1053/eupc.2002.0227
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and arrhythmia: blood pressure control and beyond

Abstract: Arrhythmias are common problems in hypertensive patients. The presence and complexity of both supraventricular and ventricular arrhythmias may influence morbidity, mortality, as well as the quality of life of patients. Diastolic dysfunction of the left ventricle, left atrial size and function, and left ventricular hypertrophy have been suggested as the underlying risk factors for supraventricular and ventricular arrhythmias in hypertensives. Recently, several non-invasive electrocardiographic parameters have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 75 publications
2
35
0
Order By: Relevance
“…Ventricular tachycardia can be found in 7-18% [26]. Some authors [24] found that concentric hypertrophy carries the greatest risk, and the eccentric a moderate risk of death and of CV complications. Nunez et al [6] found equal prevalence and complexity of ventricular arrhythmias in hypertensive patients with concentric and asymmetric LVH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ventricular tachycardia can be found in 7-18% [26]. Some authors [24] found that concentric hypertrophy carries the greatest risk, and the eccentric a moderate risk of death and of CV complications. Nunez et al [6] found equal prevalence and complexity of ventricular arrhythmias in hypertensive patients with concentric and asymmetric LVH.…”
Section: Discussionmentioning
confidence: 99%
“…The probability is that only explicitly abnormal values (i.e., those >100 ms) outside error margins may potentially have a practical value, suggesting a markedly abnormal repolarisation [23]. Scarce data was published regarding QTc interval prolongation/QTd and complex ventricular arrhythmias in hypertensive patients with LVH [24,25], but which type of LVH has the greatest influence has been understudied (especially for the asymmetric type).…”
Section: Qt Interval and Qt Dispersionmentioning
confidence: 99%
“…Besides, there was an increased incidence of impairment of left ventricular diastolic filling and left atrial enlargement [8]. The development of left ventricular hypertrophy in hypertensive patients appears to be the main link between hypertension and ventricular arrhythmias, as patients with left ventricular hypertrophy are more likely to develop ventricular arrhythmias than the hypertensive population without [56][57][58].…”
Section: Cardiac Arrhythmiasmentioning
confidence: 95%
“…It is particularly of great importance for cardiac surgeons and physicians from other specialties to be acknowledged of what and how cardiac surgical issues may develop associated with hypertension and may eventually warrant a surgical intervention. As a result, several conditions, such as coronary artery disease [3], acute aortic syndrome [4], congenital [5,6] and valvular heart disease [7], and arrhythmias [8] can be involved. The role that hypertension plays in these conditions can be complex, including hemodynamic, electrophysiological and biomolecular factors.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the case of the two patients with abnormal LPs, one can argue that the abnormal LPs resulted from other cardiovascular noxious factors such as hypertension, dyslipidemia, old myocardial infarction, or aortic stenosis, all of which are known to be associated with abnormal LPs (30)(31)(32). This suggests that FMF amyloidosis, even after long duration (seven patients had already undergone kidney replacement therapy), may spare the heart and that inflammation in FMF, with a severe enough degree to cause systemic amyloidosis, may not The late potential test was considered abnormal when two of the following criteria were met: 1) fQRS > 114 ms; 2) RMS40 < 20 μV; and 3) LAS >38 ms be sufficiently atherogenic to cause aberrant ventricular conduction.…”
Section: Discussionmentioning
confidence: 99%